1991
DOI: 10.1021/ja00023a081
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of antimony(III) and bismuth(III) chloride complexes in solution

Abstract: The search of an ideal host for the formation and detection of trapped electrons in organic single crystals has lead us to a large family of clathrate hydrates containing peralkylammonium hydroxide guests. The presence of trapped electrons has been detected by pulse radiolysis at room temperature in a large number of the clathrates.1-2 Two compounds were chosen for this initial study of electron stabilization: tetramethylammonium hydroxide pentahydrate,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(73 citation statements)
references
References 1 publication
4
69
0
Order By: Relevance
“…Its spin-forbidden character is in accordance with the observation that this emission appears only at low temperatures while the luminescence of SbCl; and BiCl; can be clearly seen in solution at room temperature [ 2,3]. A rough estimate of the radiative lifetime of AsCl; based on the emission quantum yield (@x 1 0m4) and lifetime (T= 0.46 us) yields a reasonable value of approximately 10 ms which compares with 2.5 ms for As3+ in Cs2NaScCl 6.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Its spin-forbidden character is in accordance with the observation that this emission appears only at low temperatures while the luminescence of SbCl; and BiCl; can be clearly seen in solution at room temperature [ 2,3]. A rough estimate of the radiative lifetime of AsCl; based on the emission quantum yield (@x 1 0m4) and lifetime (T= 0.46 us) yields a reasonable value of approximately 10 ms which compares with 2.5 ms for As3+ in Cs2NaScCl 6.…”
Section: Discussionsupporting
confidence: 88%
“…Stokes shifts of this magnitude were also observed for SbClb and Sic&. It is suggested that this shift is caused by a structural change from disphenoidal (C,,) [6] in the ground state toward a tetrahedral geometry in the 'P1 excited state [ 2,3]. It is quite interesting that the Stokes shift of AsCl,-is comparable to that of As3+ in Cs$IaScCl, (Ati= 12200 cm-') [ I].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The electronic spectra of SbCl 4~ (Figure 5) 10 may be used to illustrate this emission behavior. We suggest that the ground state distortion of SbCl4" is eliminated in the excited state.…”
Section: Photophysicsmentioning
confidence: 99%